1990
DOI: 10.1099/0022-1317-71-4-767
|View full text |Cite
|
Sign up to set email alerts
|

The pH independence of mammalian retrovirus infection

Abstract: The pH dependence of early steps in the infection of human and other cells by mammalian retroviruses and retroviral pseudotype particles of vesicular stomatitis virus (VSV) was investigated for 10 strains of retrovirus, including C-type and D-type oncoviruses and human lentiviruses. When cells were treated with weak bases (NH4CI and amantadine) to raise the pH of endocytic vesicles, only ecotropic murine leukaemia virus (MLV-E) and VSV showed pH-dependent entry. Pretreatment of retrovirus stocks in media below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
226
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(248 citation statements)
references
References 51 publications
(58 reference statements)
21
226
1
Order By: Relevance
“…One clue may come from the fact that, unlike many other onco-retroviruses, ecotropic virus entry has been shown in some circumstances to be pH dependent, indicating that rather than interaction at the plasma membrane, an endosomal entry route is possible. 39 Late endosomes have a low internal pH, which could be instrumental in triggering the conformational changes required for fusion.…”
Section: Discussionmentioning
confidence: 99%
“…One clue may come from the fact that, unlike many other onco-retroviruses, ecotropic virus entry has been shown in some circumstances to be pH dependent, indicating that rather than interaction at the plasma membrane, an endosomal entry route is possible. 39 Late endosomes have a low internal pH, which could be instrumental in triggering the conformational changes required for fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Virions pseudotyped with envelope proteins, such as VSV-G, which require endosomal uptake, could bypass a block which targets Nef-and gPr80-defective virions that fuse directly at the cell membrane (28,29). Interestingly, the entry of MLV-E has been described to occur via endocytic vesicles in a cell-type dependent manner (52,53), a property which might explain the target cell-dependent variability of the gPr80 activity observed on MLV-E and the lack of Nef requirement for HIV-1(MLV-E) infecting HT1080 cells. (ii) The requirement for gPr80 or Nef is similarly determined by the producer cell type (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, enveloped viruses (HSV-1, MLV, and VSV-G HIV-1) were able to infect GFP-VCA-positive cells as efficient as GFP-positive cells ( Figures 1E and 2B). In particular, when HSV-1 and ampho MLV enter cells, like HIV-1, the membrane fusion takes place at the cell surface (Fuller and Spear, 1987;McClure et al, 1990;Wittels and Spear, 1991;Nussbaum et al, 1993). These data indicated that the virus-cell membrane fusion was not inhibited by GFP-VCA.…”
Section: The Efficiency Of the Membrane Fusion Is Not Negatively Affementioning
confidence: 99%